Proses Recall Pengetahuan Oleh Siswa Autis pada Pemecahan Masalah Biologi - Muhammad Eka Setiawansyah; Aprizal Lukman; Kamid Kamid (Universitas Jambi, 2015)
The research aimed to describe the knowledge recall process of the autism student. The subject of this research is a single subject at junior high school autism student (AS), appropriate to the aim of the research. Data collecting by interview and modified thinking aloud method. The result shows that AS be able to find out and to understand problems and recalling data or information appropriately, correctly, and consistently. AS mentioned the conditions that must be fulfilled in order to conduct the problem solving strategy steps. Problem solving steps are conducted systematically to the end of problem solving process through written or oral recall process.